1987
DOI: 10.1073/pnas.84.10.3511
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y-like immunoreactivity in rat cranial parasympathetic neurons: coexistence with vasoactive intestinal peptide and choline acetyltransferase.

Abstract: Neuropeptide Y (NPY) is widely distributed in the sympathetic nervous system, where it is colocalized with norepinephrine. We report here that NPY-immunoreactive neurons are also abundant in three cranial parasympathetic ganglia, the otic, sphenopalatine, and ciliary, in the rat. Neuropeptide Y (NPY) is structurally related to members of the pancreatic polypeptide family but appears to be localized exclusively in central and peripheral neurons (1, 2). In the periphery, NPY is present in sympathetic neurons tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(63 citation statements)
references
References 27 publications
3
60
0
Order By: Relevance
“…Therefore, the present data suggest a neural control of hormonal secretion by ACh and VIP, which are released from nerve endings in contact with endocrine cells. ACh and VIP may act in synergy, as has already been observed in different tissues (LUND-BERG et al, 1980;LEBLANC et al, 1987). However, the precise mechanism of the synergic action is not known.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Therefore, the present data suggest a neural control of hormonal secretion by ACh and VIP, which are released from nerve endings in contact with endocrine cells. ACh and VIP may act in synergy, as has already been observed in different tissues (LUND-BERG et al, 1980;LEBLANC et al, 1987). However, the precise mechanism of the synergic action is not known.…”
Section: Discussionmentioning
confidence: 88%
“…Different types of nerve endings, among them cholinergic (WATARI, 1968;SHORR and BLOOM, 1970;FUJITA and KOBAYASHI, 1979) and peptidergic ones (FUJITA and KOBAYASHI, 1979) were characterized by the morphology of the synaptic vesicles they contained. The cholinergic mechanisms are presumed to be modulated by neuropeptides, including VIP (LUNDBERG et al, 1980;LEBLANC et al, 1987).…”
mentioning
confidence: 99%
“…The lack of TH-immunoreactivity in these neurons suggests that NPY is involved in non-adrenergic regulation of the peripheral tissues function. In the rat, PPG neurons expressing NPY were found to contain also VIP and/or ChAT immunoreactivity, and did not contain catecholamines and TH (Leblanc et al, 1987).…”
Section: Original Papermentioning
confidence: 97%
“…ILG VIP-containing neurons are commonly found in diverse parasympathetic ganglia as well as in local ganglia (SCHULTZBURG and LINDH, 1988;UEMURA et al, 1988) and have been suggested to mediate the vasodilatation and secretion of exocrine glands (SHIMIZU and TAIRA, 1979;LUNDBERG et al, 1980LUNDBERG et al, , 1982LUNDBERG et al, ,1984cEKSTROM et al, 1984;TOBIN et al, 1990). Coexistence of VIP and one or more different neuropeptides such as NPY, SP or CGRP in the parasympathetic ganglionic neurons is known (LEBLANC et al, 1987;DEY et al, 1988;ICHIKAWA et al, 1988;HARDEBO et al, 1992). In the intralaryngeal local ganglia of the dog, we have previously demonstrated a subpopulation of ganglionic cells containing VIP alone, VIP with NPY, VIP with SP, VIP with NPY and SP, and VIP with enkephalin (MASUKO et al, 1991).…”
Section: Innervation Of Dog Tongue 513mentioning
confidence: 99%